: Keamanan Informasi, Analisis r TANTANGAN TERKINI DALAM KEAMANAN INFORMASI ANALISIS RESIKO DAN UPAYA PERLINDUNGAN: TANTANGAN TERKINI DALAM KEAMANAN INFORMASI ANALISIS RESIKO DAN UPAYA PERLINDUNGAN - amalia, parida; Nasution, Muhammad Irwan Padli (Jurnal Manajemen, 2024)
Threats and attacks that can result in leaks of personal or sensitive data or reduced business performance have a significant impact on the security of networks and information systems. Insider attacks, eavesdropping, misconfiguration, missing functionality, confusion, man-in- attacks, virus attacks, denial of service attacks are some of the dangers that threaten your network security or threaten the security of your network. Attacks are possible. Influencing information systems. Companies risk losing information appropriate security measures, such as network and information system security. You can implement the right security solutions to predict and prevent various security risks and attacks. Confidentiality, integrity, and availability are three characteristics of security, and to determine which security technology best suits your organization's needs, you must first compare the various threats and attacks with the security technologies in use. Recommended security technologies intrusion detection systems (IDS), antivirus programs, and encryption systems. This is because this technology relies on predicting and protecting networks and information systems in many security elements.